Differential washback effects of a high-stakes test on students' English learning process: evidence from a large-scale stratified survey in China. Issue 1 (2nd January 2023) - Dong, Manxia; Fan, Jason; Xu, Jian
ABSTRACT: Understanding of the differential washback effects of high-stakes tests on students' learning remains limited. This study attempts to fill this research gap by investigating the differential washback effects of the National Matriculation English Test (NMET) in China on students' English learning process across genders, grades and English proficiency levels. A total of 3, 105 senior high school students participated in the study. An exploratory factor analysis, descriptive statistics, a t-test and a one-way ANOVA were used to analyse the data. The results showed that the NMET affected multiple facets of students' English learning motivation, learning practices, learning anxiety levels and learning time allotment. Moreover, it was revealed that the washback effects differed significantly among student subgroups defined by gender, grade and English proficiency level. The findings of this study have important implications for improving learning, teaching and test design.